Fertility and sexual activity in patients with Triple A syndrome - Dumic, Katja K.; Heinrichs, Claudine; Koehler, Katrin; Huebner, Angela; Dumic, Miroslav; Kusec, Vesna; Dusek, Tina; Quitter, Friederike (Frontiers in Endocrinology, 2024)
Objective. Triple A syndrome, caused by autosomal recessively inherited mutations in the AAAS gene is characterized by alacrima, achalasia, adrenal insufficiency, and neurological impairment. To the best of our knowledge, no patients of both sexes have been reported to have offspring. Our aim was to assess the causes of infertility in male patients with this multisystemic syndrome, and to present a female patient that spontaneously conceived a child.Design. Cross-sectional study.Methods. Six males aged 19-48 years were included. Gonadotropins, testosterone, DHEAS, androstenedione, inhibin B, anti-Mullerian hormone measurements and testicular ultrasound were performed.Results. All six male patients had impaired general health and neurological symptoms including erectile and ejaculatory dysfunction. None of them had an offspring. The only demonstrated cause of infertility in our male patients was erectile and ejaculatory dysfunction which precludes sexual intercourse. Our patients had normal libido but were sexually abstinent. Except for low adrenal androgen levels, the concentrations of all measured hormones as well as testicular ultrasound were normal which may indicate the possibility of spermatogenesis in male patients with triple A syndrome.Little is known about fertility in female patients, but based on our observations spontaneous pregnancies seem to be possible.Our results contribute to still scarce knowledge on fertility in patients with Triple A syndrome and as well represents a foundation for further research on causes of infertility and possible treatment options.